Frequency and Sensitivity of Micro-Organism in Post-Operative Wound Infections: A Quest for Microbes (Medical Forum Monthly, 2024)
Objective: To determine the frequency of common organisms involved in post- operative wound infection. To determine the sensitivity of micro-organism for different antibiotics.Study Design: prospective cross-sectional descriptive study.Place and Duration of Study: This study was conducted in 3 Surgical Units of Civil Hospital Karachi from April to September 2010.Materials and Methods: 72 swab samples were collected from patients who had undergone operations in 3 Surgical Units of Civil Hospital Karachi during a period of 6 month from April to September, 2010. Samples were obtained from the hospital and processed in Civil hospital Karachi lab (Microbiology Department).Results: Out of 72 bacterial isolates found in post-operative wound infection, 30 (41.66%) were E.Coli, followed by Klebsiella species 14 (19.44%), pseudomonas aeruginosa 13 (1.38%), staphylococcus aureus 6 (9.72%), providentia species 1 (1.38%), proteus mirabilis 1 (1.38%), Actinobacter 1 (1.38%) and no growth 6 (9.72%). The result showed that the occurrence of infection was higher in the age group between 20 -40 than any other group. There is no significant difference between male and female sexes in the occurrence of infection. Infection was more in the operation done under emergency circumstance than the elective ones.There was no significant association between infection, and co-morbidities and past history of wound infection. The sensitivity pattern of 4 main bacteria, Frequently found in the study i.e. E.coli, klebsiella, pseudomonas aeruginosa and s.aureus isolates, suggested that the organisms was more sensitive to imipenem, Amikacin sulphate, Ceftazidime, Cefperazone/Sulbactum and Pipercillin/Tazobactum than other groups of drugs.Conclusion: The most causative organism was E.coli, infection higher among the patients operated in emergency and imipenem, Amikacin sulphate were found to be more sensitive.